The power and magic of words in the literary creation of Robert Pinget and his writer-protagonists - Grzesiak, Czesław (Romanica Olomucensia, 2016)
The paper discusses the role and the functioning of words as "literary material" in Robert Pinget's literary works and in the stories of his numerous writer-protagonists. The latter, in their écriture, resort to a variety of language games, exploit polysemy, make use of lexical and syntactic variants, deform word meanings, create novel, often bizarre words, and propose funny stories. In this way, both Pinget and his protagonists demonstrate-in their literary creation-the magic and the power of words.
Keywords: Robert Pinget; creative use of language; writer; writing; language game; the Nouveau Roman.